The Relationship between Budget Knowledge and Regional Financial Supervision with Community Participation as a Moderating Variable (Empirical Study of DPRD Members in Polewali Mandar Regency) - taufik, taufik hidayat b tahawa (Kirana Publisher (KNPub), 2023)
This study aims to determine the effect of budgetary knowledge on regional financial oversight and also community participation can strengthen the relationship between board knowledge about the budget and regional financial oversight. This type of research is quantitative research. Collecting data using questionnaires. The population in this study were all 45 members of the Polewali Mandar Regency DPRD and the sample selection was carried out by the census method, so that the entire population became the sample in this study. Then the data analysis technique used is Outer Model Testing, Inner Model Testing and Hypothesis Testing using WarpPLS Software. The results of this study indicate that: Knowledge of the budget has a significant effect on regional financial oversight and community participation strengthens the relationship between board knowledge about the budget on regional financial oversight as seen from the level of the P-value which is below or equal to 0.05 and the path coefficient value in real count is greater from Path Coefficient View and P value less than 0.01.